1993
DOI: 10.1182/blood.v82.11.3392.3392
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated apoptosis in peripheral blood mononuclear cells (PBMCs) from human immunodeficiency virus type-1 infected patients and in CD4 cross-linked PBMCs from normal individuals

Abstract: This study investigates apoptosis as a mechanism for CD4+ T-cell depletion in human immunodeficiency virus type-1 (HIV-1) infection. Although several recent studies have shown that T cells of HIV-infected individuals show enhanced susceptibility to cell death by apoptosis, the mechanisms responsible for apoptosis are largely unknown. By using a flow cytometric technique and by morphology, we have quantitated the percentage of cells undergoing apoptosis in peripheral blood mononuclear cells (PBMCs) from HIV-ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
1
2

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(78 citation statements)
references
References 0 publications
3
72
1
2
Order By: Relevance
“…In contrast to our reports measuring cell death after specific activation, and to the recent analysis by Clerici et al (G. Shearer, personal communication) using recall antigens, these studies measured cell death in unstimulated culture [14,15] or in cryopreserved PBMC, after polyclonal stimulation [14,15,26]. However, this programmed cell death affects primarily CD8 T cells [13][14][15], and is not specific for AIDS [8,13,17,18], nor does it correlate with progression of disease [11,14,15]. As such, this may be of dubious relevance to disease pathogenesis.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In contrast to our reports measuring cell death after specific activation, and to the recent analysis by Clerici et al (G. Shearer, personal communication) using recall antigens, these studies measured cell death in unstimulated culture [14,15] or in cryopreserved PBMC, after polyclonal stimulation [14,15,26]. However, this programmed cell death affects primarily CD8 T cells [13][14][15], and is not specific for AIDS [8,13,17,18], nor does it correlate with progression of disease [11,14,15]. As such, this may be of dubious relevance to disease pathogenesis.…”
Section: Discussioncontrasting
confidence: 84%
“…This spontaneous cell death reflects in fact the continuous activation of the cells in vivo [11,12]. It affects primarily CD8 T cells [13][14][15], and has already been described for different acute or chronic viral pathologies like lymphocytic choriomeningitis virus infection in mice [16] or Epstein-Barr virus (EBV) infection in humans [17,18]. It does not correlate with the stage of the disease [11,12,14,15], nor is it specific for AIDS [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that the observed depletion of CD4 + cells during HIV infection involves AICD, following cross-linking of CD4 by gp120/anti-gp120 immune complexes and consequent cell death by a Fas-dependent pathway. 60 In addition, renal tubular epithelial cells are killed after HIV-1 infection, following Fas up-regulation in infected cells. 61 Levels of FasL are unaffected.…”
Section: Pathology Associated With Aberrant Fas/fasl Activitymentioning
confidence: 99%
“…Our laboratory has previously demonstrated that PBMC from HIV patients undergo accelerated apoptosis, and that crosslinking the CD4 molecule can induce apoptosis in human PBMC from normal controls (16). In addition, we have recently found that this crosslinking process upregulates the expression of Fas antigen in normal lymphocytes ( 17); others have shown that crosslinking human CD4 T cells with HIV gp120 followed by signalling through the TCR resulted in activation-dependent apoptosis (2).…”
mentioning
confidence: 99%